1993
DOI: 10.1017/s0890037x00027901
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Among Cabbage (Brassica oleraceaL.) Cultivars by Clomazone

Abstract: Excellent agreement between a two-year replicated study relative to chlorosis development by clomazone in thirty-six cabbage cultivars and development of chlorosis in a production field was obtained. The cultivars ‘Bravo’, ‘Cheers', and ‘Genesis' developed the most severe chlorosis symptoms and ‘Bently’, ‘Carlton’, ‘Cecile’, ‘Gourmet’, ‘King Cole’, ‘Ocala’, ‘Red Acre’, ‘Rio Verde’, ‘Roundup’, ‘Sombrero’, ‘Stonehead’, ‘Straton’, ‘Titanic’, and ‘Tristar’ the least chlorosis. During a dry soil period chlorosis sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 4 publications
4
13
0
Order By: Relevance
“…These findings agree with previous research that showed wide ranges in sensitivity among cultivars of the same crop for pumpkins ( Cu‐curbita spp.) [31], potatoes ( Solanum tuberosum ) [30,35], soybeans [26,27,36], cotton ( Gossypium hirsutum ) [37], dry edible beans ( Phaseolus vulgaris ) [29], and corn and cabbage ( Brassica oleracea ) [23,28]. This herbicide‐specific variation between both cultivars and species results in a low predictive ability when attempting to make accurate broad ecological risk assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings agree with previous research that showed wide ranges in sensitivity among cultivars of the same crop for pumpkins ( Cu‐curbita spp.) [31], potatoes ( Solanum tuberosum ) [30,35], soybeans [26,27,36], cotton ( Gossypium hirsutum ) [37], dry edible beans ( Phaseolus vulgaris ) [29], and corn and cabbage ( Brassica oleracea ) [23,28]. This herbicide‐specific variation between both cultivars and species results in a low predictive ability when attempting to make accurate broad ecological risk assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Any given crop species has many different cultivars, some of which may exhibit varying levels of sensitivity to a particular herbicide. It is known that levels of herbicide tolerance differ among cultivars of crops commonly used in herbicide phytotoxicity testing for regulatory purposes, such as corn [23–25] and soybean [26,27] as well as many other crop species [28–31]. This range in herbicide tolerance may result in an inaccurate representation of the phytotoxicity of the herbicide being tested, depending on which cultivar is used during the registration process.…”
Section: Introductionmentioning
confidence: 99%
“…This has also been documented in the scientific literature for maize (Zea mays) (Keifer 1989;Rowe et al, 1990;Burton et al, 1994), soybean (Glycine max) (de Weese et al, 1989;Hulting et al, 2001, Wax et al, 2006, pumpkins (Cucurbita spp.) (Harrison and Keinath, 2003), potatoes (Solanum tuberosum) (Freisen and Wall, 1984;Arsenault and Ivany, 2001), cotton (Gossypium hirsutum) (Abernathy et al, 1979), dry edible beans (Phaseolus vulgaris) (Urwin et al, 1996) and cabbage (Brassica oleracea) (Hopen et al, 1993) and is likely for many other crop species.…”
Section: Crop Varieties and Wild Ecotypesmentioning
confidence: 99%
“…However, it was shown in this study that depending on the cultivar chosen, different conclusions about the phytotoxicity of a given herbicide may differ. Harrison and Keinath (2003) found a wide range of herbicide sensitivity among 67 commercial and experimental pumpkin cultivars exposed to clomazone; Keifer (1989) and Hopen et al (1993) also found that clomazone sensitivity varied among both com and cabbage cultivars, respectively. Potato cultivars ranged in their level of sensitivity to metribuzin (Graf and Ogg, 1976;Friesen and Wall, 1984;Aresnault and Ivany, 1996;Arsenault and Ivany, 2001), as did soybeans (Wax et al, 1976;de Weese et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…For any given crop species, there are many different cultivars, some of which may exhibit varying levels of sensitivity to a particular herbicide. It is known that levels of herbicide tolerance differ among cultivars of various crop species; for example: corn (Keifer, 1989;Rowe et al, 1990;Burton et al, 1994), soybean (Wax et al, 1976;de Weese et al, 1989;Dayan et al, 1997;Hulting et al, 2001), potato (Graf and Ogg, 1976;Friesen and Wall, 1984;Aresenault and Ivany, 1996;Arsenault and Ivany, 2001), several kinds of beans (Bauer et al, 1995;Urwin et al, 1996), cotton (Abernathy et al, 1979;Molin and Khan, 1996), wheat (Bacon et al, 1986;Garcia-Baudin et al, 1990), peppers (Schroeder, 1992), pumpkins (Harrison and Keinath, 2003), cabbage (Hopen et al, 1993), collard and kale (Harrison et al, 1998), and peas (Jensen, 1993). This range in herbicide tolerance may result in an inaccurate representation of the phytotoxicity of the herbicide being tested depending on which cultivar is used during the registration process.…”
Section: Introductionmentioning
confidence: 99%